Catch and release : the enduring yet vulnerable horseshoe crab - Moore, Lisa Jean, 1967- (Book collections on Project MUSE., 2017)
"The author considers interactions between horseshoe crabs and humans, through fieldwork conducted between 2012 and 2016 at urban beaches near New York City, nature preserves in Japan, and marine research sites in Florida, and interviews with conservationists, field biologists, ecologists, and paleontologists. She explores the interspecies relationship between humans and horseshoe crabs, and how they are meaningful to one another in specific ways as humans interpret them for understanding geologic time, use them for biomedical applications, collect them for agricultural fertilizer, eat them, and capture them as bait, and crabs make humans matter by revealing humans' vulnerability to endotoxins and fertilizing soil for human food. She examines how humans exploit crabs, depend on them, and consider their welfare, discussing issues related to the species health of the horseshoe crab, their sexual reproduction, the use of their endotoxins, and global warming, site fidelity, and reclamation projects."--Provided by publisher.